2011
DOI: 10.1103/physreva.83.043408
|View full text |Cite
|
Sign up to set email alerts
|

Time-averaged adiabatic ring potential for ultracold atoms

Abstract: We report the experimental realisation of a versatile ring trap for ultracold atoms. The ring geometry is created by the time-averaged adiabatic potential resulting from the application of an oscillating magnetic bias field to a rf dressed quadrupole trap. Lifetimes for a Bose-Einstein condensate in the ring exceed 11s and the ring radius was continuously varied from 50$\mu$m to 261$\mu$m. An efficient method of loading the ring from a conventional TOP trap is presented together with a rotation scheme which in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
134
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 22 publications
0
134
0
Order By: Relevance
“…Pure static fields 20 or light fields 21,22 have also been used. However, practical atom chip schemes for interferometry with a wide dynamic range and versatile geometries are still very much sought after [23][24][25][26][27][28] . Such schemes may enable, for example, sensitive probing of classical or quantum properties of solid-state nanoscale devices and surface physics (for example, refs [29][30][31][32][33].…”
mentioning
confidence: 99%
“…Pure static fields 20 or light fields 21,22 have also been used. However, practical atom chip schemes for interferometry with a wide dynamic range and versatile geometries are still very much sought after [23][24][25][26][27][28] . Such schemes may enable, for example, sensitive probing of classical or quantum properties of solid-state nanoscale devices and surface physics (for example, refs [29][30][31][32][33].…”
mentioning
confidence: 99%
“…We expect that our trapping potential might be deformed into a ring potential after the driving phase by applying an additional optical potential [48][49][50] or using RF-field dressing techniques [51,52], which would result in a giant vortex state [33,34]. Recently, Roncaglia et al [14] showed that a giant vortex state having a large angular momentum in a ring potential is adiabatically connected to the bosonic ν = 1/2 Laughlin state in a harmonic potential.…”
Section: Discussionmentioning
confidence: 99%
“…This 'cross-talk' means that the position of the second species is also affected by the first rf component, and A relative displacement in the horizontal plane can also be achieved by manipulating the polarisation of the dressing rf field, as was previously demonstrated to tilt a single rf shell trap [30]. In this method a small vertical rf field of the form δB i sin (ω i t + φ)ê z is added to B rf , breaking the cylindrical symmetry of the coupling strength aboutê z for the i-th spheroid.…”
Section: Species Selectivity With Multiple Rfsmentioning
confidence: 99%
“…In this configuration, 85 Rb is near resonance with the field component of frequency ω 1 , and 87 Rb with that of ω 2 . Both species can be loaded simultaneously into these wells from a TimeOrbiting Potential trap, as previously demonstrated for 87 Rb in a rf-dressed potential formed with a single radiofrequency [30].…”
Section: Species Selectivity With Multiple Rfsmentioning
confidence: 99%
See 1 more Smart Citation